Penerapan Strategi Promosi Digital untuk Meningkatkan Penjualan Produk Industri Rumah Tangga Kerajinan Tangan Irig dan Kukusan Desa Arahan Kabupaten Indramayu - Durosid Durosid; Agus Yudianto; Nana Supriatna Sonjaya; Royani Royani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The bamboo handicraft home industry producing irig and kukusan in Arahan Village, Indramayu Regency, holds real economic value for the local community, yet sales remain low due to limited promotional methods and thin use of digital media. This community service activity aimed to raise product sales through participatory mentoring, training, and hands-on practice matched to the working conditions of home-based producers, covering digital marketing training, simple promotional content development, use of social media and instant messaging platforms, and ongoing support in managing promotional accounts and customer communication. Findings point to better understanding among business owners of digital promotion concepts, wider product visibility on social media, and growth in both order volume and market reach beyond the village, along with greater confidence in marketing products independently. In practical terms, the activity built up the competitiveness of home-based handicraft businesses and supported the local economy's long-term stability, offering a fuller picture of how digital promotion works as a tool for community capacity-building rooted in local strengths.